Analisis Pengaruh Motivasi Kerja dan Kompensasi terhadap Kinerja Guru Di Yayasan Makmur Al- Muthma’innah Jambi - Mustika Mustika; Apridha Nur Komariah; Andri Devita (Universitas Batanghari Jambi, 2020)
This research aims to determine: (1) The effect of work motivation and partial compensation to the teacher's performance at Yayasan Makmur Al-Muthma'innah Jambi. (2) Influence of work motivation and simultaneous compensation to the teacher's performance at Yayasan Makmur Al-Muthma'innah Jambi. This research uses methods of descriptive analysis. The Data obtained in this study used the instrument questionnaire with the number of respondents as many as 39 teachers. The data analysis methods used are multiple linear regression. From the results of the analysis can be noted that work motivation and compensation partially affect the performance, with a percentage of work motivation influence on performance by 29, 2% and for the effect of compensation to performance by 46.4%. As for the simultaneous influence of work motivation and compensation has 16.2% against performance. The motivation for work and compensation also has a positive coefficient direction of 89.0% of performance.